Residual Renal Function – How Fast Does the Residual Urine Output Function Decline in the First Year of Haemodialysis? – A Scoping Review - Steinwandel, Ulrich; Kheirkhah, Homa; Davies, Hugh (Frontiers in Nephrology, 2022)
Background: Haemodialysis is the most common treatment method in Australia for individuals requiring renal replacement therapy. Although it is known that the residual renal function in these patients has many advantages for their overall health outcomes and that the residual urine volume production is also declining over time, it is unknown how fast this functional decline occurs when patients are embarking on their first year on haemodialysis. Aim: This scoping review sought to determine if the functional decline in renal residual function in the first year of haemodialysis has been previously investigated, documented or quantified. Method: The scoping review was performed using variety of nursing and medical databases comprising MEDLINE, Embase, Web of Science and CINAHL Plus with Full Text. Results: The decline of renal residual function in patients on Peritoneal dialysis over the first year of treatment has previously been described, but not in detail for patients receiving haemodialysis. There is a paucity of knowledge how fast residual urine production can decline in patients receiving haemodialysis during their first year of treatment. A PRISMA checklist has been used to validate the results of this scoping review. Conclusions: The extended preservation of renal residual function in patients on haemodialysis is crucial for their survival and may have a positive impact on their quality of life. An observational study is needed to examine how fast the functional decrease of the residual urine production function within patients receiving haemodialysis generally occurs. This information could prove to be useful in the context of treatment goals and could inform clinical practice.